2010
DOI: 10.1159/000320719
|View full text |Cite
|
Sign up to set email alerts
|

RAR-Beta Expression Is Associated with Early Volumetric Changes to Radiation Therapy in Cervical Cancer

Abstract: manent radioresistance (p = 0.19). Conclusions: RAR-␤ expression might be a valuable marker for the prediction of early volumetric changes to RT in cervical carcinomas. Further search for additional genes associated with early volumetric changes and radioresistance may aid in refining individual treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…16 Decrease of both gene and protein expression are correlated with late response to radiotherapy in cervical cancer. 36 Checkpoint with forkhead and ring finger domains (CHFR) has recently been identified as a checkpoint protein, which safeguards mitotic entry and, therefore, affects cell cycle progression. 37 CHFR silencing leads to upregulation of PARP1, a DNA repair enzyme associated with resistance to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…16 Decrease of both gene and protein expression are correlated with late response to radiotherapy in cervical cancer. 36 Checkpoint with forkhead and ring finger domains (CHFR) has recently been identified as a checkpoint protein, which safeguards mitotic entry and, therefore, affects cell cycle progression. 37 CHFR silencing leads to upregulation of PARP1, a DNA repair enzyme associated with resistance to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The arachidonic acid metabolism was the key pathway, which was correlated with 15 reporter metabolites [67]. Kim et al performed microarray analysis of mRNA expression and found that 53 genes were differentially expressed in an early response to radiotherapy group compared with a late response group [68]. Among 53 deregulated genes, RAR-β expression is correlated to early volumetric changes to radiation therapy in cervical cancer [68].…”
Section: Systems Biology Approaches In Cervical Cancermentioning
confidence: 99%